Technical devices of improvement the technical, tactical and theoretical training of fencers - Briskin, Y.; Pityn, M.; Zadorozhna, O.; Smyrnovskyy, S.; Semeryak, Z. (Journal of Physical Education and Sport, 2014)
Proposed new training means for improving the technical, tactical and theoretical training that contribute to the growth of sports results in fencing: Simulator "TTT", which is recommended to improve the specialized technical and tactical skills of fencers on the basis of improvement of tactical thinking and specific knowledge. "Device for technical and tactical training of fencers" for improving the specialized technical and tactical skills of athletes. "Device for technical training of fencers" to improve the technical skills of fencers on the basis of improvement of specialized the feeling of the weapon.